Functional Discomfort of Earplugs and its Influencing Variables - Poissenot-Arrigoni, Bastien; Negrini, Alessia; Berbiche, Djamal; Sgard, Franck; Doutres, Olivier (Canadian Acoustics, 2023)
Earplugs are extensively used as a preventive measure against noise-induced hearing loss. Nevertheless, their effectiveness is negatively impacted by the discomfort they induce, thereby influencing their consistent and proper use. In the context of earplug use, the comfort is defined as a multidimensional construct characterized by four dimensions: ‘physical’, ‘acoustical’, ‘functional’ and ‘psychological’. The (dis)comfort results from complex interactions between the triad constituted of the person wearing the earplug, his/her earplug, and his/her work environment. The objective of this paper is to enhance the understanding of the functional (dis)comfort induced by earplugs by identifying which triad characteristics can significantly influence the two attributes of this dimension: “functionality” (i.e., a general attribute) and “efficiency” (i.e., a specific attribute). Field assessments were conducted to evaluate the (dis)comfort of earplugs, involving 173 participants who tested different earplug models over seven weeks and provided a comprehensive comfort feedback through questionnaires. Triad characteristics were evaluated both on the field mainly through questionnaires, and in laboratory using comfort testers. Statistical analyses enabled the identification of key triad characteristics that influence functional comfort. Attributes of the functional comfort considered in this study are mainly governed by characteristics of the wearer: his/her previous experience with earplugs, his/her earcanal girth and a characteristic of the work environment: the interference of the earplug with other protective equipment The findings of this study hold the potential to provide manufacturers with tools for designing earplugs considering comfort aspects, as well as to help preventionists to recommend workers with earplugs that are best suited to individuals and work environment’s characteristics.